The research into the disaxial cam mechanism for diesel fuel – injection pump - Tausenev, Evgeny; Svistula, Andrew (Transport, 2005)
A cam mechanism is named disaxial due to the offset of a plunger axis concerning the axis of a camshaft. The named offset allows to reduce the maximal angle of pressure. There is decrease of contact pressure in a pair of a cam and a roller and the pressure upon the side face of a guide sleeve. Theoretical researches into the influence of the offset and other elements of a cam mechanism on the specified pressure and kinematics of a plunger are resulted. Examples of practical realization of disaxial designs are shown. The results of comparative tests of fuel‐injection pumps with disaxial and without disaxial are shown.First Published Online: 27 Oct 2010